Assessment of oxidative stress biomarkers in patients before pharmacological treatment for rheumatoid arthritis (Acta Scientiarum. Health Sciences, 2024)
Rheumatoid Arthritis (RA) significantly decreases the functional capacity of 1% of the world's population, and it is believed that oxidative stress may be one of its triggering factors. Thus, the present study evaluated the biomarkers of oxidative stress in patients with rheumatoid arthritis before pharmacological treatment and their relationship with the DAS 28 score. This is an observational, cross-sectional study with a quantitative and analytical approach. Patients treated at a rheumatology clinic in the city of Ijuí/RS, with a diagnosis of rheumatoid arthritis, were selected and compared with the control group. Data collection took place between August and September 2020. In the 18 patients who participated in the research, higher values of SOD (p = 0.045), NP-SH (p â‰¤ 0.000) and TBARS (p = 0.005), and reduced levels of CAT (p â‰¤ 0.000) were found, when compared to the control. The enzymatic levels of the patients showed a significant association with body mass index. Furthermore, in this study, the pain complaint did not correlate with oxidative stress markers. This study showed changes in oxidative stress biomarkers in patients with RA before pharmacological treatment, demonstrating that these are indicative of a worse prognosis, which is estimated to be minimized with adequate pharmacological treatment.